Optimisation of the rearing diets for early life stages of the European lobster, Homarus gammarus, to enhance growth, survival and health using biotic dietary supplements. ... - Daniels, Carly (University of Plymouth, 2011)
The file(s) associated with this record are no longer available. [JC][04.02.2013] ... : Chapter 3 published in; Dimitroglou, A., Merrifield, D. L., Carnevali, O., Picchietti, S., Avella, M., Daniels, C., Güroy, D. and Davies, S. J. 2011: Microbial manipulations to improve fish health and production – A Mediterranean perspective. Fish & Shellfish Immunology. 30, 1-16. Chapter 4 published in:Carly L. Daniels, Daniel L. Merrifield, Dominic P. Boothroyd, Simon J. Davies, Jan R. Factor, Katie E. Arnold 2010: Effect of dietary Bacillus spp. and mannan oligosaccharides (MOS) on European lobster (Homarus gammarus L.) larvae growth performance, gut morphology and gut microbiota. Aquaculture. 304 (1-4), 49-57. ...